Zoom Cloud Meeting: Teaching Media in ESP Online Learning - Fitria Nur Hamidah; Nostalgianti Citra Prystiananta (Linguistic, English Education and Art (LEEA) Journal, 2022)
This research aims to describe the lecturers' perception of using zoom cloud meeting as a teaching medium in ESP online learning. The method of this research was descriptive qualitative. The subject of this research was the lecturers who teach ESP at State Polytechnic of Malang and University of PGRI Argopuro Jember. The results of this research showed that the lecturers could use zoom cloud meetings as a medium in teaching ESP during online learning, zoom cloud meetings could help the lecturers to teach, and it could help them to interact with the students when they did teaching and learning process. The conclusion was zoom cloud meeting has many benefits for the lecturers in ESP online learning. Keywords: Online learning, The lecturers, Zoom cloud meeting